Independent women: Shareholders in the age of the suffragettes - Graeme G. Acheson; Gareth Campbell; Áine Gallagher; John D. Turner (Queen's University Centre for Economic History (QUCEH), 2018)
The early twentieth century saw an increasingly vocal movement which campaigned for women to be able to exercise their political voices independently of men. This coincided with more women participating directly in the stock market. In this paper we analyse whether these female shareholders acted independently of men. We reject the hypothesis that they were heavily influenced by male associates. Using a novel dataset of 500,000 shareholders in some of the largest British railways, we find that women were much more likely to be solo shareholders than men. There is also evidence that they prioritised their independence above other considerations such as where they invested or how diversified they could be. However, we find that they were deliberately excluded from being eligible for election to boards of directors.
Keywords: G10; J16; N23; 330; Gender; Investment; Stock Market; Railways